Navigating Respect and Rapport: A Comparative Analysis of Teacher and Student Politeness Strategies in EFL Classroom - Helda Oktaviani; Siti Suharsih; Abdul Azis (Journal of English Language Studies, 2024)
This study investigates how politeness strategies are used by teacher and students in the context of learning and teaching English in a tenth-grade high school in Banten's Lebak district. A qualitative research method was applied using field observation, field recording and note-taking as data collection techniques. The data were obtained from recordings of teacher and students' utterances in an EFL class in a tenth-grade high school. The resulting data were transcribed based on the tone of voice and body language used by teacher and students then analyzed using the interactive model and pragmatic equivalence method. The findings showed that teacher and students apply politeness strategies from Brown and Levinson's theory namely, positive politeness strategy, and negative politeness strategy.